Block Cipher Design： Generalized Single-Use-Algorithm Based on Chaos - Zhao, Geng; Chen, Guanrong; Fang, Jingqing; Xu, Gang (Tsinghua science and technology, 2011)
The idea of using a one-time-one-key design has been widely applied in conventional cryptography. With the security theory of conventional cryptology, encryption algorithms are made public while all the secrets are encoded only in the keys. This paper applies chaos theory to conventional cryptography to develop a one-time-one-algorithm design. A general theory is given to generate the clock key, substitution box, permutation box and operational sign functions for a one-time-one-algorithm scheme. This scheme is then implemented in a system to manage the tradeoff between speed and the security of the encryption algorithm.